Regulation of CorA Mg(2+) Channel Function Affects the Virulence of Salmonella enterica Serovar Typhimurium - Papp-Wallace, Krisztina M. (American Society for Microbiology (ASM), 2008)
The CorA Mg(2+) channel is the primary source of intracellular Mg(2+) in Salmonella enterica serovar Typhimurium. In another study, we found that a strain lacking corA was attenuated in mice and also defective for invasion and replication within Caco-2 epithelial cells (K. M. Papp-Wallace, M. Nartea, D. G. Kehres, S. Porwollik, M. McClelland, S. J. Libby, F. C. Fang, and M. E. Maguire, J. Bacteriol. 190:6517-6523, 2008). Therefore, we further examined Salmonella interaction with Caco-2 epithelial cells. Inhibiting CorA acutely or chronically with a high concentration of a selective inhibitor, Co(III) hexaammine, had no effect on S. enterica serovar Typhimurium invasion of Caco-2 epithelial cells. Complementing the corA mutation with corA from various species rescued the invasion defect only if the complementing allele was functional and if it was evolutionarily similar to S. enterica serovar Typhimurium CorA. One explanation for these results could be that regulation of CorA function is needed for optimal virulence. Further experiments examining corA transcription, CorA protein content, CorA transport, and cell Mg(2+) content indicated that both CorA expression and CorA function are differentially regulated. Moreover, the rates of Mg(2+) influx via CorA are not closely correlated with either protein levels or Mg(2+) content. We conclude that loss of the CorA protein disrupts a regulatory network(s) with the ultimate phenotype of decreased virulence. This conclusion is compatible with the microarray results in our other study, which showed that loss of corA resulted in changes in transcription (and protein expression) in multiple metabolic pathways (Papp-Wallace et al., J. Bacteriol. 190:6517-6523, 2008). Further study of the regulation of CorA expression and function provides an opportunity to dissect the complexity of Mg(2+) homeostasis and its ties to virulence within the bacterium.